Effects of decolonization on bilateral trade: Evidence from natural experiments. Issue 4 (19th May 2022) - Yin Ho, Cheuk
Abstract : This paper estimates the effects of decolonization on bilateral trade by exploiting the end of colonial linkages between the United Kingdom and Hong Kong in 1997 and between Portugal and Macau in 1999. The two-year gap between these two historical events creates an exogenous time variation in colonial separations across colonial pairs to implement the differences-in-differences strategy. The results show that if a colonial relationship breaks up, then the imports from the former colonial counterpart increases by 42 percent and the post-colonial trade share increases by 0.29 percentage points. Further investigations suggest that the large and positive effects of decolonization on the post-colonial imports are largely operated through mechanisms of income and exchange rate.